2022
DOI: 10.3390/foods11121776
|View full text |Cite
|
Sign up to set email alerts
|

Spoilage Potential of Contaminating Yeast Species Kluyveromyces marxianus, Pichia kudriavzevii and Torulaspora delbrueckii during Cold Storage of Skyr

Abstract: This study investigated the spoilage potential of yeast strains Kluyveromyces marxianus (Km1, Km2 and Km3), Pichia kudriavzevii Pk1 and Torulaspora delbrueckii Td1 grown in skyr in cold storage. Yeast strains were isolated from skyr and identified by sequencing of the 26S rRNA gene. K. marxianus yeasts were grown in skyr to high numbers, generating large amounts of volatile organic compounds (VOC) associated with off-flavours, among them were alcohols (3-methyl-1-butanol, 2-methyl-1-propanol and 1-hexanol), es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 80 publications
2
6
0
Order By: Relevance
“…Meanwhile, sample 2, showing similar enumeration results but a very low gas formation, was dominated by P. kudriavzevii . Gas production by these two microorganisms in this project is also in agreement with a previous study (Srimahaeak et al., 2022).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Meanwhile, sample 2, showing similar enumeration results but a very low gas formation, was dominated by P. kudriavzevii . Gas production by these two microorganisms in this project is also in agreement with a previous study (Srimahaeak et al., 2022).…”
Section: Resultssupporting
confidence: 93%
“…In spite of the fact that a variety of microorganisms especially spore‐forming bacteria that are able to stand the two‐step pasteurization were identified in this project and other studies, it was shown here that yeasts as the post‐pasteurization contaminants were the most dominant isolates in non‐carbonated and pasteurized industrial yogurt drink. With respect to the present results, C. parapsilosis was previously reported to be responsible for the spoilage in yogurt drink, in addition to K. marxianus and P. kudriavzevii indicated as the spoilage agents in an Icelandic dairy product called skyr (Anari et al., 2022; Srimahaeak et al., 2022).…”
Section: Resultssupporting
confidence: 70%
“…However, the isolates had not caused disease and the species identification is uncertain. Srimahaeak et al (2022) demonstrated a dairy products spoilage potential of three K. marxianus strains isolated from skyr (an Icelandic dairy product similar to yoghurt).…”
Section: Kluyveromyces Marxianusmentioning
confidence: 99%
“…Srimahaeak et al. ( 2022 ) demonstrated a dairy products spoilage potential of three K. marxianus strains isolated from skyr (an Icelandic dairy product similar to yoghurt).…”
Section: Assessmentmentioning
confidence: 99%
“…P. kudriavzevii has been isolated from several indigenous fermented milk products from different areas, although it was reported to be lactase-negative [ 38 , 39 , 40 , 41 ]. Several studies highlighted the spoilage potential of P. kudriavzevii because of its film-forming property under acidic conditions, and the release of alcohols and esters thought to be associated with off-flavors of fermented milk beverages [ 42 , 43 ]. On the other hand, P. kudriavzevii from a traditional fermented cow milk in Colombia was reported to produce peptides with Angiotensin I converting enzyme (ACE) inhibitory activity, which has the effect of lowering blood pressure [ 44 ].…”
Section: Application In Fermented Foods and Feed Industrymentioning
confidence: 99%